Methodological strategy for asynchronous learning mathematical operations with real numbers - Espinoza-Pinos, Carlos (2022)
Consolidating the skills to use concepts, properties, and procedures based on algorithms or heuristics and analysis to solve challenging situations is of great importance for students in their learning. This article aims to propose a methodological strategy based on adaptive learning to facilitate the solution of combined operations with real numbers in eighth-grade students of basic general education. The mixed method uses questionnaires applied to students and teachers to collect data. The diagnosis determines that students do not master the basic competencies to work basic operations with real numbers. The teachers agree with the need to apply innovative strategies that promote learning in mathematics. It is concluded that it is imperative to update the planning of content with activities that help motivate students to learn mathematics, considering that not everyone learns at the same pace.